Bruh Rabbit and the tar baby girl - Hamilton, Virginia, 1934-2002 (Blue Sky Press, 2003)
In this retelling, using Gullah speech, of a familiar story the wily Brer Rabbit outwits Brer Fox who has set out to trap him.